Status of antibiotic resistant salmonella typhi strains from clinical isolates in Dhaka - Shariar, Mohammad; Kabir, Shaila (Dhaka University Journal of Biological Sciences, 2011)
Key words: Salmonella typhi; Antimicrobial sensitivity; Clinical isolates DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8966 DUJBS 2010; 19(2): 207-209